PENGAWASAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DALAM ALIH FUNGSI LAHAN DI KECAMATAN CIMAHI UTARA KOTA CIMAHI - Irma Safei (Jurnal Caraka Prabu, 2018)
This research is entitled “ The Supervision Of Public Works and Spatial Planning In Over The Conversion Land In North Cimahi Subdistrict Of Cimahi City”. The limitations problem in this study is not yet optimal controlling by Publick Works Control and Spatial Planning in the North Bandung Area. Then the research can be detail by identification the problem as follow : How the controlling of Public Works and Spatial Planning of Cimahi City areas in maintainance the availability of land that conversion does not occur continuously in? The method used in this reseach by using descriptive method of analysis with qualitative approach. While the technique on data collection is done through, literature study, interview, observation and by studying the local regulation, and performed data analysis techniques with three stages of data reduction, data presentation and conclusion. The interview was conducted in this reseach to Head of the Spatial Use Control Section, Head of North Cimahi Subdistrict and Staff of Permissions The Spatial Section. While the main instrument in this reseach is the researcher themselves. Based on the result of the research is population growth became one of the facts of conversion land, controls conducted by Department of Public Works and Spatial Planning has not been optimal because it has not been able to act witch regulations and commitment to built in to implement local regulations with the spatial fungction which resulted in land conversion occurred in The Area of North Bandung; North Cimahi Subdistrict; Cimahi City.